Energy efficiency optimization based on household electric water heater aggregation considering user comfort. Issue 11 (29th August 2018) - Wu, Xin; Liang, Kaixin
Abstract : With the development of new energy power generation, consumption of new energy has become a tricky problem. The aim of this letter is to develop an energy efficiency optimization method considering user comfort, specifically for household electric water heaters (HEWHs), which is effective to improve utilization associated with the new energy. The control cycle is calculated based on aggregate cycling load models, which is not affected by the comfortable conditions of using HEWHs. And, we develop a model to approach the target profile representing power needed to consume, then select the optimal combination of the model using the artificial immune algorithm, calculating the weight coefficient of components in combination using the least squares method. The validity of the method is verified using experiment. © 2018 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.